Automatic CFD analysis method for shape optimization (2007)
This project presents an Automatic Computational Fluid Dynamics (CFD) analysis method for shape optimization of an aerodynamic profile -- It begins with an overview of basic concepts on shape optimization, geometry parameterization and objective functions -- It continues with an introduction to the current status of CFD simulation software and types of solvers -- Then expands to optimization based on CFD analysis -- Following, a CFD-based method to optimize aerodynamic profiles under certain restrictions and scenarios is proposed -- Finally, the code implemented to automatically modify a profile bound by a set of control points based on CFD analysis is described -- The project was developed entirely at the EAFIT University’s Applied Mechanics Laboratory in Medellin, Colombia and is part of a collaboration effort in companionship with the University of Aberta in Canada and Los Andes University in Bogota, Colombia